Envolvimento dos receptores AT1 e do óxido nítrico na ingestão de NaCl 0,5 M e nas respostas dipsogênicas, renais e pressoras produzidas pela angiotensina II injetada na área septal lateral - Garcia, Gustavo (2006)
In this study, we investigated the participation of the AT1 receptors and of the nitric oxide (NO) into lateral septal area (LSA), on the water intake, 0,5 M NaCl intake, natriuresis, diuresis and pressor response induced by injection of angiotensin II (ANG II) in the same area. Male Holtzman rats were used weighing between 280 and 320 g, with cannulae of stainless steel implanted stereotactically into the LSA. The ANG II (25 ng/0,5 µl) injected into LSA, induced water and sodium intake and increased the urinary volume, sodium urinary excretion and arterial pressure when compared with the control group, that received 0,15 M NaCl. The pretreatment with losartan (antagonist of the AT1 angiotensin receptors) into LSA abolished the water intake, the sodium intake and the pressor effect induced by ANG II. The losartan also reduced the increase of urinary volume and of the sodium excretion induced by ANG II. The previous treatment with 7-nitroindazole (inhibit of the nitric oxide synthase enzyme) abolished the water intake and the increase of urinary volume, decreased the sodium intake and the natriuretic effect and no changed the pressor effect induced by ANG II. The results show the involvement of the AT1 angiotensinergic receptors and of the nitric oxide into LSA in the control of the cardiovascular and hydroelectrolytic balance, beyond a possible interaction between nitrergic and angiotensinergic mechanisms of the LSA in this control.